Managing agricultural intensification: The role of international research - Dar, William D.; Twomlow, Stephen J. (Crop protection, 2007)
Over the next 20–25 yr, global food demand is expected to increase by around 50%, largely due to demand in developing countries. The challenge is to increase production without damaging the natural resource base. Various technologies for integrated natural resource management (INRM) have been developed, but adoption has been poor, for various reasons—technical, socio-economic, and institutional. To date a great deal of past work has focused at the plot and farm level, with little farmer involvement in developing the research agenda. Work needs to be extrapolated to more sites, with greater farmer involvement in the research process, in order to answer the key question: ‘Under what conditions will rural households be encouraged to reinvest in their agroecosystems?’ Encouraging such investment involves several challenges: improving returns from such investments; creating market access for smallholder farmers; improving research–extension–farmer linkages; developing enabling policies on soil, water and biodiversity; integration of livestock–wildlife–crop systems; development of drought mitigation strategies; capacity building; better information flow; and a clearer gender perspective in research and training. A large body of successful INRM research is available from many countries in the West and in Latin America. Unfortunately much of this work is reaching sub-Saharan Africa only now, and its appropriateness to the needs of the African smallholder farmer requires verification. This paper shares some of the experiences of the Consultative Group on International Agricultural Research (CGIAR), International Agricultural Research Centers (IARCs) in Africa, particularly the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT). Reference is made to some specific technologies and some limited successes with small-scale farmers in Africa.